2023
DOI: 10.3390/horticulturae9091060
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Compatibility and Environmental Conditions on Soilless Eggplant (Solanum melongena) Grown in the Mediterranean Greenhouse

Sergio Argento,
Simone Treccarichi,
Maria Grazia Melilli
et al.

Abstract: Grafting techniques represent an efficient tool to enhance plant growth and development. The study aims to explore the effects of different grafting combinations on the growth of eggplants under diverse greenhouse conditions. Eggplant cultivar Black bell (Bb) was employed as scion, while the hybrid F1 Beaufort (Be) and Solanum torvum (To) were utilized as rootstock. The hypothesis behind this study pertains to grafting incompatibility with Beaufort F1. It postulates that this incompatibility can be mitigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
2
0
0
Order By: Relevance
“…In our study, the combination of the Black Bell cultivar grafted onto the Beaufort F1 rootstock (Be/Bb) exhibited the highest vegetative growth, as evidenced by parameters like plant height (PH), rootstock basal diameter (PBDR and PBDS), and grafting point diameter. This outcome aligns with previous studies where the Beaufort F1 rootstock has typically shown incompatibility with various eggplant cultivars, resulting in excessive vegetative development [40][41][42]. Conversely, the combination of the S. torvum rootstock with the Black Bell scion (To/Bb) displayed substantial vegetative traits, particularly a notable increase in scion basal diameter (PBDS).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the combination of the Black Bell cultivar grafted onto the Beaufort F1 rootstock (Be/Bb) exhibited the highest vegetative growth, as evidenced by parameters like plant height (PH), rootstock basal diameter (PBDR and PBDS), and grafting point diameter. This outcome aligns with previous studies where the Beaufort F1 rootstock has typically shown incompatibility with various eggplant cultivars, resulting in excessive vegetative development [40][41][42]. Conversely, the combination of the S. torvum rootstock with the Black Bell scion (To/Bb) displayed substantial vegetative traits, particularly a notable increase in scion basal diameter (PBDS).…”
Section: Discussionsupporting
confidence: 89%
“…Notably, the combination with S. torvum rootstock displayed the highest FP value. This higher FP value can be attributed to the strong compatibility between S. melongena grafted onto S. torvum rootstock, as supported by various studies [42,44,53]. Additionally, under IR50 conditions, we observed the highest FP value, which is likely due to the reduced vegetative growth of IR50 plants, which addressed a faster transition to the reproductive stage.…”
Section: Discussionsupporting
confidence: 81%